PENGARUH NON PERFORMING LOAN, RETURN ON ASSETS, DAN CAPITAL ADEQUACY RATIO TERHADAP CADANGAN KERUGIAN PENURUNAN NILAI BANK KONVENSIONAL DI BURSA EFEK INDONESIA - YOSAR HARITSAR (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2021)
The background of this research is the influence of the banking sector in Indonesia which is quite large on economic development and state finance because it functions as an institution capable of channeling funds owned by surplus economic units to deficit economic units. Potential investors who want to invest in banking companies could take various factors into consideration, including the Loan Loss Provision. This study aims to determine the effect of non-performing loan ratio, return on assets ratio and capital adequacy ratio to loan loss provision. This analysis will later be used as a reference for owners, investors, customers, and other related parties. Of the 43 companies in the banking sector, there are 36 sample companies and will be analyzed from 2017 to 2019. The data source to be used is the annual report of the sample companies. This type of research uses a quantitative approach with multiple linear regression methods processed with the SPSS version 22 program. The results show that the two variables, both non-performing loan ratio and return on assets ratio have a positive effect on loan loss provision, while the capital adequacy ratio does not affect the loan loss provision.